Photomath application for learning algebra: Preliminary study on a school in border area - Siahaan, Meiva Marthaulina Lestari; Salsinha, Cecilia Novianti; Hijriani, Lailin; Nahak, Selestina; Daniel, Farida (Universitas Islam Negeri Raden Intan Lampung, 2025)
This research was motivated by the shift in the educational paradigm toward technology-integrated learning and addresses the disparity in facilities between urban and border area schools. It aimed to determine the effect of Photomath on students' cognitive abilities and to assess their attitudes, motivation, belief, and readiness towards its use in a border area school. The instruments employed were pretest, posttest, and questionnaire. This research serves as an initial study on the use of technology in schools located in border areas. A mixed-method approach was employed, combining qualitative and quantitative analyses. The qualitative analysis of student responses was facilitated by Photomath, while the quantitative method followed a pre-experimental one-group pretest-posttest design. The findings showed a 36.25% improvement in algebra test scores. Students’ learning motivation reached 82.97% (very strong), belief in Photomath was 88.13% (very strong), and readiness to use the Photomath was 78.97% (strong). After using Photomath, students understood each stage of solving algebra problems better, indicating that Photomath supported their learning process. The implication is that integrating Photomath in border-area schools provides valuable support for students, particularly in self-directed learning.